Radiosynthesis and Tumor MicroPET/CT Imaging of 18F-Fluoroethoxylerianin, an 18F-Labeled Erianin Analogue - Nie, Hui; Wang, Nian; Huang, Jinwen; Ni, Zhuang; Xue, Kangyan; Song, Lixing; Wang, Mingwei; Wu, Fanhong (SynOpen, 2022)
Erianin is an active constituent of Dendrobium candidum. In this work, 18F-fluoroethoxylerianin ([18F]FEE), a 18F-Labeled erianin analogue, was designed and synthesized to evaluate the properties of erianin and related analogues by in vivo PET imaging. The initial product was separated and purified by liquid-phase separation module Explora LC and simple homemade solid-phase extraction, and high purity [18F]FEE was finally obtained. The radiochemical purity of [18F]FEE was determined by Radio-TLC and Radio-HPLC. [18F]FEE showed good stability in normal saline and serum, and could be quickly eliminated from mice. Cell experiments, biological distribution, and small-animal PET/CT further showed that [18F]FEE had a high uptake rate in HepG2 tumor cells, and showed good imaging ability in a HepG2 tumor model. The results of this study indicate that the synthesized 18F-labeled erianin analogue is an effective new probe for positron emission tomography (PET) imaging of HepG2 hepatocellular carcinoma, which provides an intuitive and reliable theoretical basis for the development of erianin as an anticancer drug.
Keywords: fluorine-18; radiosynthesis; microPET/CT; tumors; erianin